Reflective thinking in early childhood education - Morris, Joanne B., 1952- (2000)
Thesis (M.Ed.)--Memorial University of Newfoundland, 2000. Education Bibliography: leaves 123-134 This study considers the reflective thinking of early childhood education students at the end of the first year of a two-year diploma program at the provincial college in Newfoundland and Labrador. Reflective thinking has been found to be a means of internalizing theory, reflecting on practice, and learning meaningful ways to improve and change practice. Graduates are expected to demonstrate knowledge of theories and practices necessary to plan and implement curriculum for individual children and groups in early childhood settings. A qualitative research design was selected to determine descriptive evidence of reflective thinking levels and behaviours for the 7 early childhood education students who comprised the study group. The students, who were selected from a population of 72, ranged in age from 20-58 with an average age of 37 years. There were 6 females and 1 male. Data were collected while students were engaged in discussion groups, guided journal writing, and discussions of observations of practice. There was evidence of 622 reflective thinking responses in total. The researcher concludes that these early childhood education students, at the end of the first year of a two-year diploma program, engaged in reflective thinking. The researcher recommends further research and provides recommendations to faculty involved in early childhood education.